Increased virulence of the oral microbiome in oral squamous cell carcinoma revealed by metatranscriptome analyses. Issue 4 (December 2018) - Yost, Susan; Stashenko, Philip; Choi, Yoonhee; Kukuruzinska, Maria; Genco, Caroline; Salama, Andrew; Weinberg, Ellen; Kramer, Carolyn; Frias-Lopez, Jorge
Abstract Oral squamous cell carcinoma (OSCC) is the most prevalent and most commonly studied oral cancer. However, there is a void regarding the role that the oral microbiome may play in OSCC. Although the relationship between microbial community composition and OSCC has been thoroughly investigated, microbial profiles of the human microbiome in cancer are understudied. Here we performed a small pilot study of community-wide metatranscriptome analysis to profile mRNA expression in the entire oral microbiome in OSCC to reveal molecular functions associated with this disease.Fusobacteria showed a statistically significantly higher number of transcripts at tumour sites and tumour-adjacent sites of cancer patients compared to the healthy controls analysed. Regardless of the community composition, specific metabolic signatures were consistently found in disease. Activities such as iron ion transport, tryptophanase activity, peptidase activities and superoxide dismutase were over-represented in tumour and tumour-adjacent samples when compared to the healthy controls. The expression of putative virulence factors in the oral communities associated with OSCC showed that activities related to capsule biosynthesis, flagellum synthesis and assembly, chemotaxis, iron transport, haemolysins and adhesins were upregulated at tumour sites. Moreover, activities associated with protection against reactive nitrogen intermediates, chemotaxis, flagellar and capsule biosynthesis were also upregulated in non-tumour sites of cancer patients. Although they are preliminary, our results further suggest thatFusobacteria may be the leading phylogenetic group responsible for the increase in expression of virulence factors in the oral microbiome of OSCC patients. Oncology: bacteria may contribute to oral cancer development A search of the oral microbiome has revealed a group of bacteria closely associated with the most common type of oral cancer, and whose activity may play a role in its development. Oral squamous cell carcinoma (OSCC) has been linked to tobacco and alcohol consumption, but there's increasing interest in the role bacteria might play in its initiation and growth. To better understand the behaviour of the various microbes present in the mouths of healthy people and those with OSCC, Jorge Frias-Lopez at the University of Florida in Gainesville and his colleagues carried out a metatranscriptome analysis, which identifies the most actively expressed genes. This revealed significant differences in their microbial communities, withFusidobacteria particularly enriched and hyperactive in patients with OSCC. The team also identified microbial activities that were consistently associated with cancer.